BIMBINGAN BELAJAR BERKUALITAS DI SATO ANAK PINTAR: MEMBANGUN PONDASI PENDIDIKAN INTERNASIONAL BALI - Waruwu, Opirman (Haga : Jurnal Pengabdian Kepada Masyarakat, 2024)
Quality education is a key factor in shaping a generation capable of competing on a global scale. The Quality Learning Guidance Program at SATO Anak Pintar aims to establish an educational foundation that aligns with international standards in Bali. This program adopts innovative teaching methods, such as constructivist approaches, collaborative learning, personalized learning, as well as the utilization of educational technology and problem-based learning (PBL). Additionally, the program aims to introduce students to global perspectives through multicultural education and character development. The results of the program’s implementation show significant improvements in academic performance, social skills, and collaboration abilities among students. Challenges related to technology infrastructure and varying learning styles are addressed by providing additional devices and employing a flexible approach to teaching. This program is expected to make a tangible contribution to improving the quality of education in Bali and preparing young people to compete internationally.